The Effect of Islamic Social Reporting on Firm Value (Case Study on Islamic Banks In Indonesia) - Rahmawati Khoiriyah (Kusuma Negara Business School, 2020)
This study aims to determine the effect of islamic social reporting against firm value. The development of ISR includes five themes, they are social, labor, enviroment, corporate governance and service/ product. This study identified 43 disclosure index items of ISR main theme. Data analysis using multiple linier regression. The data used is secondary data obtained form annual reports of islamic banks registered on Bank Umum Syariah by taking a sample of 12 islamis banks. The result indicate that islamic social reporting simultaneously influences firm value. Partially only 3 indicators that have effect on firm value, they are social influence of 0,07977; labor influence of 0,11304; and environment influence of 0,15579.